Acacetin Protects Against High Glucose-Induced Endothelial Cells Injury by Preserving Mitochondrial Function via Activating Sirt1/Sirt3/AMPK Signals - Wei-Min Han; Xu-Chang Chen; Gui-Rong Li; Gui-Rong Li; Yan Wang (Frontiers Media S.A., 2020)
The strategy of decreasing atherosclerotic cardiovascular disorder is imperative for reducing premature death and improving quality of life in patients with diabetes mellitus. The aim of this study was to investigate whether the natural flavone acacetin could protect against endothelial injury induced by high glucose and attenuate diabetes-accelerated atherosclerosis in streptozotocin-(STZ) induced diabetic ApoE−/− mice model. It was found that in human umbilical vein endothelial cells (HUVECs) cultured with normal 5.5 mM or high 33 mM glucose, acacetin (0.3-3 μM) exerted strong cytoprotective effects by reversing high glucose-induced viability reduction and reducing apoptosis and excess production of intracellular reactive oxygen species (ROS) and malondialdehyde in a concentration-dependent manner. Acacetin countered high glucose-induced depolarization of mitochondrial membrane potential and reduction of ATP product and mitoBcl-2/mitoBax ratio. Silencing Sirt3 abolished the beneficial effects of acacetin. Further analysis revealed that these effects of acacetin rely on Sirt1 activation by increasing NAD+ followed by increasing Sirt3, pAMPK and PGC-1α. In STZ-diabetic mice, acacetin significantly upregulated the decreased signaling molecules (i.e. SOD, Bcl-2, PGC-1α, pAMPK, Sirt3 and Sirt1) in aorta tissue and attenuated atherosclerosis. These results indicate that vascular endothelial protection of acacetin by activating Sirt1/Sirt3/AMPK signals is likely involved in alleviating diabetes-accelerated atherosclerosis by preserving mitochondrial function, which suggests that acacetin may be a drug candidate for treating cardiovascular disorder in patients with diabetes.